2019
DOI: 10.1002/jum.15197
|View full text |Cite
|
Sign up to set email alerts
|

Overview of ultrasound applications for assessing scrotal disorders

Abstract: The scrotum may be affected by a plethora of different disorders such as infections, vasculopathies, trauma, and manifestations of primary and secondary malignant masses. In addition to the patient's medical history and clinical examination, ultrasound represents the imaging modality of choice to assess scrotal disorders. Timeconsuming contrast-enhanced ultrasound and elastography can provide further information to distinguish between benign and malignant testicular mass lesions. The following invited Special … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…It is defined as an abnormal dilatations of the pampiniform plexus with reflux of venous blood flow (>2–3 mm in diameter) caused by insufficiency or absence of valves; however, when diagnosed during adult age, it could be correlated to several conditions (hydronephrosis, hepatic cirrhosis, nutcracker syndrome 27 ) including neoplastic mass compressing spermatic veins, so exams to rule out a secondary varicocoele should be performed (Figure 3). Varicocoele is in general asymptomatic, but may present with pain, enlarged scrotum, and infertility/subfertility, and a “bag of worms” appearance is often detected on palpation 28–31 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is defined as an abnormal dilatations of the pampiniform plexus with reflux of venous blood flow (>2–3 mm in diameter) caused by insufficiency or absence of valves; however, when diagnosed during adult age, it could be correlated to several conditions (hydronephrosis, hepatic cirrhosis, nutcracker syndrome 27 ) including neoplastic mass compressing spermatic veins, so exams to rule out a secondary varicocoele should be performed (Figure 3). Varicocoele is in general asymptomatic, but may present with pain, enlarged scrotum, and infertility/subfertility, and a “bag of worms” appearance is often detected on palpation 28–31 …”
Section: Resultsmentioning
confidence: 99%
“…Varicocoele is in general asymptomatic, but may present with pain, enlarged scrotum, and infertility/subfertility, and a "bag of worms" appearance is often detected on palpation. [28][29][30][31] B-mode ultrasound is able to detect venous dilation with varicose appearance both within scrotum and along inguinal canal, while CDUS with spectral analysis allows to visualize vein flow and persistent reflux The use of SE has found as well that testicles affected by varicocoele are stiffer than contralateral healthy ones or case controls. 40,41 Caretta et al assessed with CEUS 90 patients affected by varicocoele and found that a mean transit time higher than 36 s was correlated with oligospermia, with 78% sensitivity and 58% specificity.…”
Section: Varicocoelementioning
confidence: 99%
“…Ultrasound examination can also indicate the physical examination and add to its diagnosis value. It is remarkably helpful in cases when full trans-illumination cannot be fully observed or in cases when the size of the hydrocele intervenes with the thorough examination of the scrotal surface, to exclude the presence of scrotal tumors [12][13][14][15]. Moreover, although most cases with communicating hydrocele are asymptomatic, some patients might develop symptoms, and in such cases, imaging should be conducted for these patients to assess the presence of a potential underlying etiology [12,16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scrotal ultrasonography (US), with a combination of grayscale and color Doppler US, is the first-line imaging technique for the evaluation of testicular pathology, due to its low cost, wide availability, convenience, short examination time, lack of radiation exposure, and high diagnostic accuracy [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. This technique represents the initial imaging diagnostic tool for the confirmation of the presence of a testicular mass and for the evaluation of the contralateral testis, and is strongly recommended, even in the presence of a clinically evident testicular tumor [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, US has limitations related to the operator’s practice and clinical experience, along with its relatively small field of view and lack of adequate tissue characterization. Occasionally, scrotal US findings are equivocal or nonspecific, including indeterminate nature of a testicular mass, difficulties in delineating lesions’ location and/or extension, and discrepancies between US findings and clinical history [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 9 ]. Multiparametric US—including conventional US, contrast-enhanced US, and elastography—has significantly improved the diagnostic efficacy of the technique in the assessment of scrotal diseases [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%